Measuring Services Quality of Ski Resorts: an approach to identify the consumer profile - Miragaia, D. A. M. (2016)
This study determined the consumer’s profile in winter sports, using their degree of satisfaction with services provided by a ski resort. A questionnaire was administered to 229 tourists/visitors and analyzed their satisfaction according to five factors: facilities and equipment; attributes of the slopes; resort services; restaurants, accommodation and social activities; and also about the access to the resort. Determination between levels of satisfaction indicated by different consumer segments was performed using a cluster analysis. The clusters identified were partially satisfied, dissatisfied, dissatisfied with everything, satisfied with everything. In relation to gender, no significant differences were identified in any cluster. With regard to expe-rience to visited other ski resorts, significant differences were found between tourists/visitors which have already done, comparing with the individuals who never been a similar context. It was found that only 5.2% of consumers who have had similar experiences with other ski resorts were satisfied with all services provided. The results of this study enable to the managers identify the attributes by which tourists/visitors have a higher level of satisfaction/dissatisfaction and foremost identify the valences which can be subject to some kind of improvement. This approach enables the adaptation of services according the preferences and expectations of tourists/visitors, with the prospect of incrementing consumer loyalty.